PENGARUH BAURAN PROMOSI TERHADAP KEPUTUSAN MAHASISWA MEMILIH UNIVERSITAS MUHAMMADIYAH PALEMBANG (UMP) - Fitantina, Fitantina; Mahrom, Yudha; Annanta, M Alief (Universitas Muhammadiyah Palembang, 2021)
Purpose –This research was conducted with the aim of knowing the effect of promotional mix on student decision to choose Universitas Muhammadiyah Palembang (UMP). Design/methodology –The The type of research was descriptive. The population in this study was 9,781 people using solvin formula obtained 100 samples. The sampling technique was purposive sampling. The types of data were primary and secondary data. Data collection methods used Questionnaires and Document Analysis. Data analysis used quantitative qualitative data. Analysis techniques used Multiple Linear Regression Analysis, F Hypothesis Test and T Hypothesis Test, as well as Determination Coefficient. .Findings - The result of this research showed that 1) there was an effect of promotional mix (Advertising, Sales Promotion, Publicity, Face-to-Face Sales, and Public Relations) on student decision to choose UMP, 2) there was an effect of advertising on student decision to choose Universitas Muhammadiyah Palembang, 3) there was no effect of sales promotion on student decision to Choose Universitas Muhammadiyah Palembang, 4) there was no publicity effect on student decision to choose Universitas Muhammadiyah Palembang, 5) there was an effect of face-to-face sales on student decision to choose Universitas Muhammadiyah Palembang, 6) there was no effect of public relations on student decisions to choose Universitas Muhammadiyah Palembang.